The TatD-like DNase of Plasmodium is a virulence factor and a potential malaria vaccine candidate - Zhiguang Chang (Nature Portfolio, 2016)
Neutrophil extracellular traps (NETs), composed of DNA and proteases, contribute to the innate immune response by capturing pathogens. Here, Chang et al. identify a NET-degrading DNase in Plasmodiumparasites and show that immunization with this protein provides protective immunity in a malaria mouse model.